Working Capital Turnover, Leverage, And Operating Cash Flow As Determinants Of Liquidity In Food and Beverage Companies In Indonesia - Ega Octarinjani; Ima Andriyani; Sahila; Kusminaini Armin (CV Putra Publisher, 2026)
This study aims to analyze the effects of Working Capital Turnover (WCT), Debt-to-Asset Ratio (DAR), and Operating Cash Flow (OCF) on corporate liquidity, as proxied by the Current Ratio (CR). The study population includes all companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. Using purposive sampling, a final sample of 7 companies was obtained, comprising a total of 140 panel data observations, which were analyzed using SPSS. The data analysis techniques applied included descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, the coefficient of determination test, and hypothesis testing (t-test and F-test). The results of the partial tests (t-tests) show that WCT has a positive and significant effect on CR (beta = 0.209); (Sig. = 0.00), and OCF has a positive and significant effect on CR (beta = 0.195); (Sig. = 0.012). Conversely, DAR was found to have a negative and significant effect on CR (beta = -0.507); (Sig. = 0.000) and was the most dominant variable influencing liquidity. Simultaneously (F-test), all three independent variables had a significant effect on CR with an F-value of 42.991 (Sig. = 0.000). The Adjusted R-Square value of 0.787 indicates that 78.7% of the variation in liquidity can be explained by this model, while the remainder is influenced by other factors outside the scope of this study. Management is advised to optimize working capital turnover and maintain a balanced debt structure to ensure the company’s liquidity stability. The implementation of the research findings emphasizes the need for management to improve working capital efficiency by accelerating the cash cycle and limiting the asset-based debt ratio to maintain liquidity stability.